LUTI modelling in the Netherlands: Experiences with TIGRIS and a framework for a new LUTI model - Schoemakers, Arnout; van der Hoorn, Toon (European Journal of Transport and Infrastructure Research, 2004)
This paper presents the use of the Dutch LUTI model TIGRIS in the planning process. TIGRIS is a long-term, incremental, time-based interaction and allocation model for land use, mobility, congestion and accessibility. In TIGRIS accessibility is described as a location factor for land-use that generates mobility. This increased mobility leads to congestion and changes in accessibility, and afterwards to new changes in land use. The model is used for regional and national forecasting, and follows a learning-by-doing approach. In this paper four applications of TIGRIS are described with a focus on assessing impacts and the role in the planning process. Because TIGRIS was originally developed as a sketch planning model with limited detail and the calibration on the basis of empirical data was rather limited, a new version, TIGRIS XL, is currently being developed.